Pretreatments as a key for enzymatic hydrolysis of lignocellulosic biomass - Rabelo, Sarita Cândida [UNESP] (2023)
Enzymatic hydrolysis of lignocellulosic materials has shown several advantages over chemical hydrolysis to obtain oligo- and monosaccharides, as well as derivatives to produce either biofuels or high-value products. The enzymatic hydrolysis step is strongly influenced by the choice of pretreatment as it affects all the biomass factors that define the accessibility of cellulose by enzymes. In this chapter, a review of the factors that affect enzymatic hydrolysis and their relationship with the choice of pretreatment will be presented. The advantages and disadvantages of the main types of pretreatments available in the literature will be discussed, as well as issues related to their cost, production of inhibitor compounds, and type of biomass fractionation.